Noise from the writing center - Boquet, Elizabeth, author; Utah State University Press, publisher (Colorado State University. Libraries, 2002)
In Noise from the Writing Center, Boquet develops a theory of ''noise'' and excess as an important element of difference between the pedagogy of writing centers and the academy in general. Addressing administrative issues, Boquet strains against the bean-counting anxiety that seems to drive so much of writing center administration.
Tutoring as (hard) labor: the writing clinic, the writing laboratory, the writing center -- Channeling Jimi Hendrix, or ghosts in the feedback machine -- Toward a performative pedagogy in the writing center -- Conclusion: thanks for listening, folks.
Keywords: English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching (Higher); Tutors and tutoring; Writing centers